RECOMMENDATIONS ON CULTURAL HERITAGE SITE MANAGEMENT PLAN FOR THE PUNJULHARJO BOAT IN REMBANG, CENTRAL JAVA: REKOMENDASI RANCANGAN PENGELOLAAN SITUS CAGAR BUDAYA PERAHU PUNJULHARJO DI REMBANG, JAWA TENGAH - Agni Sesaria Mochtar (Berkala Arkeologi, 2020)
Abstract The Punjulharjo boat is a wooden watercraft, built in the traditional Southeast Asian boat building technique called lashed-lug tradition. It was found in 2008, excavated, and later was dismantled for a lengthy conservation process. In early 2018, the hull was reassembled to be displayed for public. The site where the boat was found, and now displayed, has been listed as a heritage site under the Regulation of The Minister of Culture and Tourism No. 57 of 2010, but a management plan of it is still non-existent. Recommendations in this proposed management plan was amassed in accordance to international standards on site management plan. Data was collected from direct site observation, with the assistance of consultations to related references. This plan outlines objectives and strategy in managing the Punjulharjo site, and hopefully can serve as guidelines for the Regional Government of the District of Rembang as the manager of the site. Abstrak Perahu kayu Punjulharjo adalah salah satu alat transportasi air tradisional yang dibuat dengan teknik tambuku-terikat khas Asia Tenggara. Perahu ini ditemukan pada tahun 2008, kemudian dieksvasi dan setelahnya dibongkar untuk dikonservasi dalam proses yang cukup panjang. Pada awal tahun 2018, kayu-kayu lambung kapal direkonstruksi dan dipamerkan kepada masyarakat. Perahu ini telah ditetapkan sebagai situs cagar budaya berdasarkan Peraturan Menteri Kebudayaan dan Pariwisata No.57 tahun 2010. Akan tetapi, belum ada perencanaan pengelolaan yang dapat menjamin kelestarian situs Perahu Punjulharjo ini.Â Rekomendasi dalam rancangan pengelolaan ini disusun dengan mengacu pada standar international rencana pengelolaan situs cagar budaya. Data untuk penyusunan rencana pengelolaan ini diperoleh dari pengamatan langsung di situs dan dilengkapi dengan penelusuran referensi terkait. Rencana pengelolaan ini menjabarkan strategi dan langkah-langkah pengelolaan yang perlu diterapkan untuk perlindungan dan pelestarian situs, yang diharapkan dapat digunakan sebagai acuan bagi Pemerintah Daerah Kabupaten Rembang sebagai pengelola situs perahu Punjulharjo.